Evaluation of the success of mathematics teacher candidates in 2001-2004 university entrance examination in Turkey - Muzaffer Okur; Ramazan Dikici (Penerbit ukm, 2006)
In this study, the knowledge and skills that Mathematics Teacher Candidate (MTC) students should gain to solve the mathematics questions in the University Entrance Examinations (UEE)1 between the years 2001 and 2004, and the rate of success have been examined. For this purpose, mathematics questions of UEE of last four years have been applied to a group of 593 MTC students that are currently at Kazim Karabekir Education Faculty and Faculty of Arts and Sciences in Atatürk University. At the end of the assessment, the rate of students’ success in answering questions related to permutation and combination, three-dimensional geometry was found out to be low. In addition, we also determined the distribution of the questions according to the subjects in the curriculum and their conformity in terms of content and level